On statistical mechanics in noncommutative spaces - Alavi, S.A. (Вопросы атомной науки и техники, 2007)
We study the formulation of quantum statistical mechanics in noncommutative spaces. We construct microcanonical and canonical ensemble theory in noncommutative spaces and study some basic and important examples in the framework of noncommutative statistical mechanics.